Chemical generation and modification of peptides containing multiple dehydroalanines. Issue 70 (29th July 2015) - Morrison, Philip M.; Foley, Patrick J.; Warriner, Stuart L.; Webb, Michael E.
Abstract : Development of an effective strategy to convert multiple cysteines into dehydroalanine residues within a single peptide using methyl dibromovalerate. Abstract : Chemical formation of dehydroalanine has been widely used for the post-translational modification of proteins and peptides, however methods to incorporate multiple dehydroalanine residues into a single peptide have not been defined. We report the use of methyl 2, 5-dibromovalerate which can be used to cleanly carry out this transformation.